2017
DOI: 10.1186/s13099-016-0150-0
|View full text |Cite
|
Sign up to set email alerts
|

The complete genome sequence of Cronobacter sakazakii ATCC 29544T, a food-borne pathogen, isolated from a child’s throat

Abstract: Background Cronobacter sakazakii is an emerging opportunistic pathogen that is associated with rare but life-threatening cases of severe diseases: meningitis, necrotizing enterocolitis, and sepsis in premature and full-term infants. However, the pathogenesis mechanism of this pathogen remains largely unknown. To determine its pathogenesis at the genomic level, the genome of C. sakazakii ATCC 29544T was completely sequenced and analyzed.ResultsThe genomic DNA, containing a circular chromosome and three plasmids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 36 publications
0
11
0
4
Order By: Relevance
“…Interestingly, phage T4 encodes a tightly regulated and almost complete nucleotide biosynthesis pathway that reflects the low GC content of T4 DNA [55,56]. Similarly, the S144 genes encoding for the pyrimidine pathway may allow the phage to synthetize a genome with a lower GC content (45.8%) compared to its hosts, S. enterica (approximatively 52%) [57] and C. sakazakii (approximatively 57%) [58]. When it comes to transcription, phage S144 uses the host RNA polymerase to initiate transcription of its own genes, like phages T4 and Lambda do [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, phage T4 encodes a tightly regulated and almost complete nucleotide biosynthesis pathway that reflects the low GC content of T4 DNA [55,56]. Similarly, the S144 genes encoding for the pyrimidine pathway may allow the phage to synthetize a genome with a lower GC content (45.8%) compared to its hosts, S. enterica (approximatively 52%) [57] and C. sakazakii (approximatively 57%) [58]. When it comes to transcription, phage S144 uses the host RNA polymerase to initiate transcription of its own genes, like phages T4 and Lambda do [59].…”
Section: Discussionmentioning
confidence: 99%
“…The promoter host and score calculated by PhagePromoter are available in the full annnotation table, available as Supplementary material. Putative spanins have been identified with the spanin tools in CPT Galaxy and curated as suggested by Kongari [58,80]. The genome was visualised with DNA Plotter [81].…”
Section: Genome Assembly and Bioinformatic Analysismentioning
confidence: 99%
“…In the presence of predisposing factors, the strains that produce the pore-forming NetB toxin can lead to the production of necrotic enteritis, as this toxin is essential for the disease to occur when predisposing factors are present ( Rood et al., 2018 ). Recent reports have shown that the pathogenesis and virulence of C. perfringens are also controlled by other genes or loci ( Coursodon et al., 2012 ; Zhou et al., 2017 ) and these factors could contribute to the different severity levels of the NE disease.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Cronobacter currently contains seven species, namely C. malonaticus, C. turicensis, C. muytjensii, C. dublinensis, C. condimenti, C. universalis, and C. sakazakii. Cronobacter sakazakii is widely regarded as an opportunistic pathogen causing life-threatening invasive infections, particularly in neonates (13)(14)(15) and the elderly (16). Clinical manifestations include necrotizing enterocolitis, septicemia, and meningitis, with fatality rates as high as 80% being reported.…”
mentioning
confidence: 99%